2015
DOI: 10.1111/adb.12236
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A-mediated AKT signaling in the dentate gyrus contributes to the acquisition, expression and reinstatement of morphine-induced conditioned place preference

Abstract: Accumulating evidence indicates that the hippocampal dentate gyrus (DG), a critical brain region contributing to learning and memory, is involved in the addiction and relapse to abused drugs. Emerging studies also suggest the role of orexin signaling in the rewarding behavior induced by repeated exposure to opiates. In the present study, we investigated the dynamic adaptation of orexin signaling in the DG and its functional significance in the acquisition, expression, maintenance of and relapse to rewarding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…It has been shown that dopaminergic, GABAergic, glutamatergic, serotonergic, adrenergic and orexinergic pathways along with endogen opioid peptides are involved in the reward and reinforcement pathway (4,5,9). One of the most important systems that is involved in the addiction and relapse to drugs of abuse is the dopaminergic system, which begins from the ventral tegmental area (VTA) with projections to nucleus accumbens (NAcc).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dopaminergic, GABAergic, glutamatergic, serotonergic, adrenergic and orexinergic pathways along with endogen opioid peptides are involved in the reward and reinforcement pathway (4,5,9). One of the most important systems that is involved in the addiction and relapse to drugs of abuse is the dopaminergic system, which begins from the ventral tegmental area (VTA) with projections to nucleus accumbens (NAcc).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, during CPP testing, entrance to the drug‐paired context is preceded by phase‐locked hippocampal theta rhythm (Takano, Tanaka, Takano, & Hironaka, ), suggesting the involvement of the hippocampus in reward memory retrieval of contextual cues. On a causative level, pharmacological disruptions or lesions of the hippocampus and dentate gyrus interfere with many stages of CPP, including the acquisition and retrieval of the drug/context association (Ebrahimian et al, ; Ferbinteanu & McDonald, ; Guo et al, ; Hernández‐Rabaza et al, ; Hitchcock & Lattal, ; Katebi, Farahimanesh, Fatahi, Zarrabian, & Haghparast, ; Meyers, Zavala, & Neisewander, ; Meyers, Zavala, Speer, & Neisewander, ; Milekic, Brown, Castellini, & Alberini, ; Rezayof, Zatali, Haeri‐Rohani, & Zarrindast, ; Sadeghi, Ezzatpanah, & Haghparast, ; Taubenfeld, Muravieva, Garcia‐Osta, & Alberini, ; Zarrindast, Nouri, & Ahmadi, ), and interfere with other animal models of addiction‐relevant behaviors (Fuchs et al, ; Ramirez et al, ; Paniccia et al, ). Such studies in laboratory animals support that the hippocampus and dentate gyrus play an important role in context‐dependent reward memory (Smith & Bulkin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reinstatement model has been extensively used as animal model of relapse to drug seeking (See et al, ). The conditioned place preference (CPP) paradigm can be used to indicate reinstatement of place preference by stress or a priming drug after an extinction period (Guo et al, ; Lu et al, ; Parker and Mcdonald, ; Sinha, ). Generally, foot shock has been used as stressor to induce behavioral reinstatement in the stress‐reinstatement model (Shaham et al, ).…”
Section: Introductionmentioning
confidence: 99%